Risk management in G7 contruction company - Ili Hazwani Binti Ramli (School of Environmental Engineering, University Malaysia Perlis, 2014)
Construction projects are full with complexity and uncertainties that coming from various sources. Generally, all industry is involved with risk and it is the concern for the construction company. In construction industry, it is emphasis to implement risk management to minimize the risk in the projects. The objectives of this study are to study and analyzing the risk management in G7 construction company, to identify the primary risk considered by the contractor before participating in construction bidding and to examine the mitigation measures to manage each category of risk.